Analisis Akuntansi Likuidasi Terhadap Persekutuan Karena Datangnya Anggota Baru dan Keluarnya Anggota Lama - Lintang Ababil Abilowo; Shoofii Arum Almirah; Herlina Rumiyati (Jurnal Kendali Akuntansi, 2024)
This research examines the accounting analysis of partnership liquidation due to changes in membership, both from the entry of new members and the departure of existing members. The main focus of the study is to understand the concept of partnership liquidation, the procedures involved, and the required accounting records.The research background emphasizes the importance of accounting in providing accurate financial information for decision-making. This study also discusses conditions that can lead to the dissolution of partnerships, such as the death of a member or changes in membership composition.The research methodology includes analysis of literature related to partnership liquidation. The main objectives of the research are to explain the definition of partnership liquidation, outline the liquidation procedures, and describe the accounting recording process in the context of partnership liquidation.This research aims to provide a comprehensive understanding of the partnership liquidation process and its implications for accounting practices, as well as contribute to the development of student competencies in the field of accounting.